THE INFLUENCE OF INTERNAL CONTROLS, ETHICS, FINANCIAL PRESSURE, AND INDEPENDENT COMMISSIONERS ON FINANCIAL STATEMENT FRAUD - Muhammad Rizky; Anis Chariri (Diponegoro Journal of Accounting, 2026)
This study examines the effects of internal control systems, corporate code of ethics implementation, financial pressure, and the proportion of independent commissioners on financial statement fraud. Using a quantitative approach, secondary data were collected from annual reports of financial sector companies listed on the Indonesia Stock Exchange during 2021–2023. The sample was selected using purposive sampling, and the data were analyzed through multiple linear regression with SPSS 26. The results indicate that internal control systems, corporate code of ethics implementation, and the proportion of independent commissioners have significant negative effects on financial statement fraud, suggesting that stronger governance mechanisms reduce the likelihood of fraudulent financial reporting. In contrast, financial pressure has a significant positive effect on financial statement fraud, indicating that firms experiencing greater financial pressure are more likely to engage in fraudulent reporting practices.